Magical Realism in Hussain’s "The Swan’s Wife": An Examination from a Postmodern Angle - Khan, Sadaf; Zahoor, Sahar; Khan, Maryam (Pakistan Journal of Humanities and Social Sciences, 2024)
The utilization of magical realism is pertinent to the postcolonial context and the consequent expression of dissent against the impact of postcolonialism on the political, social, and cultural aspects of formerly colonized countries. Magical realism, characterized as subversive, hybrid, and mestizo, has been recognized as a powerful means of social protest. Nevertheless, there has been a lack of comprehensive scholarly attention on the correlation between magical realism and social protest in the works of Hussain. This thesis examines the manner in which magical realism has aided Hussain in portraying and capturing the essence of "The Swan's Wife". The author's use of magical realism in his work has a clear and noticeable political aspect. It not only prompts the reader to question the supposedly fixed nature of reality, but also examines the boundaries of an implicitly politicized ideology that undermines the fundamental framework of his worldview. This theme investigation aims to illustrate that Hussain's fiction not only has explicit social consequences but also carries a subtle tone of protest against the social structure. To create the appropriate level of protest, the author used magical realism. This technique involves incorporating and contrasting different components from many sources, such as oral/folklore culture, myth, and stereotypes.